HOW TRAINING, NUTRITION, SLEEP, AND RECOVERY IMPROVE PERFORMANCE. - Zuhur Mansurov (International Journal of Literature and Language Studies, 2026)
This article examines how the four essential pillars of athletic performance—training, nutrition, sleep, and recovery—work together to enhance physical abilities and long-term sporting success. It explains the scientific principles behind effective training, including progressive overload, specificity, and periodisation, while highlighting the importance of balanced nutrition, proper hydration, and nutrient timing in supporting performance and adaptation. The article also explores the crucial role of sleep in muscle repair, cognitive function, and hormonal regulation, as well as the significance of recovery strategies such as active recovery, stretching, rest, and mental relaxation. Finally, it demonstrates that sustainable athletic excellence depends on maintaining a balance among these interconnected factors, enabling athletes of all levels to maximise performance, reduce injury risk, and promote overall health and well-being.